How do you prove #(cscx + cotx)^2 = (1 + cosx) / (1 - cosx)#?

Answer 1

in this manner.

The initial participant is:

#(1/sinx+cosx/sinx)^2=(1+cosx)^2/sin^2x=(1+cosx)^2/(1-cos^2x)=#
#(1+cosx)^2/((1+cosx)(1-cosx))=(1+cosx)/(1-cosx)#,

That makes up the second participant.

Sign up to view the whole answer

By signing up, you agree to our Terms of Service and Privacy Policy

Sign up with email
Answer 2
#(csc x + cotx)^2#
= #(1/sin x + cos x/ sin x)^2#
= # (1+cosx)^2 / sin^2 x#
= #(1+cos x)^2 /(1-cos^2x)#
=#(1+cosx)^2 /((1+cos x)(1-cos x))#
= # (1+cos x)/(1-cosx)# = RHS
Sign up to view the whole answer

By signing up, you agree to our Terms of Service and Privacy Policy

Sign up with email
Answer 3

To prove the trigonometric identity ( (\csc x + \cot x)^2 = \frac{1 + \cos x}{1 - \cos x} ), follow these steps:

Start with the left-hand side (LHS) of the equation: [ (\csc x + \cot x)^2 ]

Expand and simplify the expression: [ (\csc x + \cot x)^2 = \csc^2 x + 2\csc x \cot x + \cot^2 x ]

Use the trigonometric identities: [ \csc^2 x = \frac{1}{\sin^2 x} ] [ \cot x = \frac{\cos x}{\sin x} ] [ \cot^2 x = \left( \frac{\cos x}{\sin x} \right)^2 = \frac{\cos^2 x}{\sin^2 x} ]

Substitute these identities into the expression: [ \frac{1}{\sin^2 x} + 2\frac{\cos x}{\sin x} \cdot \frac{\cos x}{\sin x} + \frac{\cos^2 x}{\sin^2 x} ]

Combine the fractions: [ \frac{1}{\sin^2 x} + \frac{2\cos^2 x}{\sin^2 x} + \frac{\cos^2 x}{\sin^2 x} ]

Combine the terms: [ \frac{1 + 3\cos^2 x}{\sin^2 x} ]

Now, use the Pythagorean identity ( 1 = \sin^2 x + \cos^2 x ) to simplify further: [ 1 + 3\cos^2 x = \sin^2 x + 3\cos^2 x = \sin^2 x + 3(1 - \sin^2 x) ] [ = \sin^2 x + 3 - 3\sin^2 x = 3 - 2\sin^2 x ]

Substitute this back into the expression: [ \frac{3 - 2\sin^2 x}{\sin^2 x} = \frac{3 - 2(1 - \cos^2 x)}{1 - \cos^2 x} ] [ = \frac{3 - 2 + 2\cos^2 x}{1 - \cos^2 x} = \frac{1 + 2\cos^2 x}{1 - \cos^2 x} ]

Since ( 1 - \cos^2 x = \sin^2 x ), the expression simplifies to: [ \frac{1 + \cos x}{1 - \cos x} ]

This is the same as the right-hand side (RHS) of the equation, so the identity is proven.

Sign up to view the whole answer

By signing up, you agree to our Terms of Service and Privacy Policy

Sign up with email
Answer from HIX Tutor

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

Not the question you need?

Drag image here or click to upload

Or press Ctrl + V to paste
Answer Background
HIX Tutor
Solve ANY homework problem with a smart AI
  • 98% accuracy study help
  • Covers math, physics, chemistry, biology, and more
  • Step-by-step, in-depth guides
  • Readily available 24/7